The Effect of EDAPP as LMS on Students' English Proficiency on Junior High School Student - putra, aldino maulana (RETAIN : Journal of Research in English Language Teaching, 2023)
The purpose of this study was to examine the effect of EDAPP, an educational mobile application, on student English proficiency. A sample of 26 students from a Junior High school participated in the study .Pre- and post-test measures were administered to assess their English proficiency in four language skills: reading, writing, listening, and speaking Using english Score .The findings of the study revealed a significant improvement in the English proficiency of the students. The student  show higher scores in all four language skills, indicating the positive impact of EDAPP on their language learning outcomes. Moreover, the student satisfaction surveys indicated a high level of engagement and motivation among the experimental group. The interactive features,     gamification elements, and user-friendly interface of EDAPP were reported to enhance their learning experience and foster a positive attitude towards language learning. These findings suggest that the integration of EDAPP in English language instruction can be an effective approach to enhance student English proficiency. The mobile application's interactive and engaging nature provides students with opportunities for self-paced learning, immediate feedback, and personalized practice, thereby promoting their language skills development .Further research is recommended to explore the long-term effects of EDAPP on student English proficiency, as well as to investigate its effectiveness in different educational settings and with diverse learner populations.